Effects of a mobile health nutrition intervention on dietary intake in children who have autism spectrum disorder - Kral, Tanja V. E.; O’Malley, Lauren; Johnson, Kelsey; Benvenuti, Teresa; Chittams, Jesse; Quinn, Ryan J.; Thomas, J. Graham; Pinto-Martin, Jennifer A.; Levy, Susan E.; Kuschner, Emily S. (Frontiers in Pediatrics, 2023)
Background: Children who have Autism Spectrum Disorder (ASD) show preferences for processed foods, such as salty and sugary snacks (SSS) and sugar-sweetened beverages (SSB), while healthier foods, such as fruits and vegetables (FV), are consumed less. Innovative tools are needed that can efficiently disseminate evidence-based interventions and engage autistic children to improve their diet. Aim: The aim of this 3-month randomized trial was to test the initial efficacy of a mobile health (mHealth) nutrition intervention on changing consumption of targeted healthy (FV) and less healthy foods/beverages (SSS, SSB) in children who have ASD, ages 6-10, who were picky eaters. Methods: Thirty-eight parent-child dyads were randomly assigned to either an intervention (technology) group or a wait list control (education) group. The intervention included behavioral skills training, a high level of personalization for dietary goals, and involved parents as “agents of change.” Parents in the education group received general nutrition education and the dietary goals but did not receive skills training. Children’s intake was assessed at baseline and at 3 months using 24-hour dietary recalls. Results: While there were no significant group-by-time interactions (P>0.25) for any of the primary outcomes, we found a significant main effect of time for FV intake (P=0.04) indicating that both groups consumed more FV at 3 months (2.58 ± 0.30 servings/day) than at baseline (2.17 ± 0.28 servings/day; P=0.03). Children in the intervention group who consumed few FV at baseline and showed high engagement with the technology increased their FV intake by 1.5 servings/day (P<0.01). Children’s taste/smell sensitivity significantly predicted their FV intake (P=0.0446); for each unit of lower taste/smell sensitivity (indicating greater sensory processing abnormalities), FV intake increased by 0.13 ± 0.1 servings/day. Discussion: This mHealth intervention did not yield significant between-group differences for changing consumption of targeted foods/beverages. Only children who consumed few FV at baseline and highly engaged with the technology increased their FV intake at 3 months. Future research should test additional strategies to expand the intervention’s impact on a wider range of foods while also reaching a broader group of children who have ASD. This trial was registered at clinicaltrials.gov as NCT03424811.